Étude de la Sensibilité Aux Huiles Essentielles de Cinnamomum Verum, Eucalyptus Globulus, et Glycyrrhiza Glabra L Ainsi qu’aux Antibiotiques de Certains Germes Issus de la Restauration Collective - Samoussa, Milan Oba; Abdellaoui, Abderrazak; Kettani, Anass; Saile, Rachid; Bennani, Houda (European Scientific Journal, ESJ, 2018)
Food safety is still a very important topic of interest. The use of medicinal plants extracts can be an efficient alternative for fighting food-borne infections in the face of the increase of resistance to antibiotics. We have studied the sensitivity of bacterial strains isolated from food outlets using commonly used antibiotics (Amoxicillin, Vancomycin, Ceftriaxone, Teicoplanin, Rifampicin and Amikacin). This was done using an antibiogram. We have also tested their sensitivity against essential oils extracted from medicinal plants (Cinnamomum verum, Eucalyptus globulus, and Glycyrrhiza glabra L) using aromatogram. This study was conducted using 27 bacterial strains, including 9 Escherichia coli strains, 9 Staphylococcus aureus strains, 9 Salmonella spp. strains, and 3 ATCC strains (E. coli ATCC 25922, Staphylococcus aureus ATCC 25923 et Salmonella typhimurium ATCC 14028). Results revealed that two plant extracts has a substantial antibacterial activity with zones of inhibition ranging from 10 to 25 mm, and it reached 35 mm when using a cocktail of plant extracts. Regarding the antibiotics we used, all strains of Salmonella spp. demonstrated a resistance to amoxicillin and to ceftriaxone. The tested strains of E. coli and Staphylococcus aureus had a partial resistance to the tested antibiotics, which confirms the results of previous studies.